Yang Patah tumbuh, Yang Hilang Berganti: Figuratives in a Banda Neira’s Songs - Chairina Nasir; Kismullah Abdul Muthalib; Magfirah Fitri (Proceedings of AICS - Social Sciences, 2021)
Songs are made up from lyrics and tone which function to entertain and to deliver messages. Often time song’s lyrics contain metaphorical language as the way to express ideas and emotions. This research discusses the use of figurative language in Banda Neira’s album yang patah tumbuh, yang hilang berganti. It looks at the types of figurative language and messages conveyed in the song lyrics. Data was taken from the songs collection in the album. This is a qualitative study using document analysis as its technique of data collection. The research found figurative language was used thirty times in five songs analyzed from Banda Neira’s album. The types of figurative language use were classified based on Keraf’s figurative language framework (2009). The results of the research show that the forty times of the figurative language used can be divided into nine types. This paper discusses these types with examples found in the songs. This research is hoped to offer more insights to the understanding of how different ways of figurative language use can add to the beauty and aesthetical elements of literary works by looking closely Banda Neira’s songs in the album.Keywords: type of figurative language, Banda Neira’s songs, song lyrics analysis.